Platelet-leukocyte aggregate formation and inflammation in patients with pulmonary arterial hypertension and CTEPH. (17th November 2022) - Åberg, Mikael; Björklund, Erik; Wikström, Gerhard; Christersson, Christina
Abstract: Pulmonary hypertension (PH) is defined by increased mean pulmonary artery pressure, and the clinical classification includes five etiologies, of which we investigated subgroup 1, pulmonary arterial hypertension (PAH) and subgroup 4, chronic thrombotic and/or embolic disease (CTEPH). Platelets participate in both innate and adaptive immune responses and could possibly contribute to the suggested systemic inflammation associated with PAH. In this study, we utilized flow cytometry to analyze platelet activation and platelet-monocyte (PMA) and granulocyte (PGA) aggregates in PAH and CTEPH patients and healthy control subjects. The plasma concentration of proinflammatory cytokines was measured by multiplex electrochemiluminescence. Our main finding is that circulating platelets are activated in the circulation and form aggregates with both monocytes and granulocytes in patients with idiopathic PAH (IPAH), associated PAH (APAH) and pulmonary hypertension due to CTEPH. There was a strong correlation between the platelet activation, assessed as P-selectin, and the number of aggregates formed. IL-6, IL-8, IL-10 and TNF-α were increased in all PH subgroups as compared to healthy controls, and PMAs were associated with circulating IL-6, IL-8 and IL-10, whereas PGAs were associated with IL-6. The increased concentrations of platelet-leukocyte aggregates found in PAH/CTEPH patients might thus contribute to the inflammatory state in PH.